José Saramago as a transiberianist cultural translator - Baltrusch, Burghard (Rassegna Iberistica, 2023)
Saramago left behind his conviction that “we are all translators” and that “writing means translating”. This article aims to show that many aspects of Saramago’s life and work can be approached from a translational perspective, as there is still a gap of critical literature on the subject. Saramago’s thought on translation will be first explained in general terms, through a brief comparison with Walter Benjamin, and then specifically in terms of cultural translation, through what he understood as iberism and transibericity. The numerous texts and interviews in which Saramago reflected on intra- and extra-Iberian relations allow us to analyse him today as a cultural translator. He defended the necessity of an intra-Iberian solidarity capable of preserving differentiated identities, and drew our attention to the need for a trans-Iberian political-cultural translation. I will argue that Saramago translated Luso and Spanish ethnocentrism into three key ideas. Firstly, the multicultural character of the Iberian Peninsula, which is a historically incontestable fact. Secondly, that Iberian cultures, without making them uniform, would share a common basis that differentiates them, in turn, from Europe. And thirdly the idea of transibericity as a “task of translating, while respecting the place from which [we] came and the place to which [we] are going” (Saramago 2003, n.p.), as a dialogue with the alternative doxa that today include Latin American and African post-colonial cultures.